Evaluating Organizational Commitment in Higher Education through Models Analysis - Onia, Saifaldin Idris (Pancasila International Journal of Applied Social Science, 2025)
The concept of organizational commitment has gained currency over the last few years and has become the primary cornerstone in both management and behavior sciences. To this importance, this paper strived to shed light on the concept of organizational commitment in higher education and review of some related models and theories of organizational commitment. The paper concludes that organizational commitment is essential in any institution because highly organizationally committed staff can demonstrate positive work behaviors. The paper reviewed several models of organizational commitment. O'Reilly and Chatman’s model concluded that commitment took three types: compliance, identification, and internalization. Morrow’s model identifies five major commitments: affective organizational commitment, continued organizational commitment, career commitment, employee involvement, and work ethic. Etzioni’s model of organizational commitment encompasses three perspectives, namely: moral commitment, calculative commitment, and alienative commitment. Meyer and Allen’s three-component model referred to as being affective, continuance, and normative commitment.